Der Einfluss des Besuches religiöser Veranstaltungen auf die soziale Integration von christlichen und muslimischen Migranten der ersten Generation - Müssig, Stephanie; Stichs, Anja (Religiöser Pluralismus im Fokus quantitativer Religionsforschung, 2012)

Die vergessene Geschichte des Islam in Bayern - Jonker, Gerdientje; Nowar, Nina; Müssig, Stephanie (2018)

Discrimination and Civic Engagement of Immigrants in Western Societies. A Systematic Scoping Review - Müssig, Stephanie; Okrug, Inken (Journal of International Migration and Integration, 2024)
Research has highlighted the barriers that immigrants face due to discrimination in their everyday lives. At the same time, it has been shown that immigrants get civically engaged to counteract discrimination and to work for structural change. To contribute to ongoing research on how discrimination affects attitudes, behaviour, and eventually life opportunities of immigrants, we investigate in a scoping review conceptualisations and measurements of discrimination and civic engagement used in empirical quantitative studies. We take systematic stock of publications that examine the link between discrimination—perceived and experienced—and the civic engagement of immigrants in Western societies. Using three of the leading databases for the social sciences, we systematically search for literature on discrimination and civic engagement over the past 50 years. On the basis of the retrieved publications, we assess how studies conceptualise and measure discrimination and civic engagement and investigate how scholars represent the link between discrimination and civic engagement in their statistical models. We introduce an analytical framework for discrimination that leads to more analytical clarity and may serve as a tool to investigate the link between discrimination and civic engagement more precisely. From our review, we derive recommendations as to how studies from different disciplines can learn and benefit from each other in order to gather knowledge on the mechanisms that underlie the link between discrimination and civic engagement.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Civic engagement; Discrimination; Immigrants; Muslim; Participation

Editorial Introduction: Migration und Religion - Müssig, Stephanie; Pickel, Gert (Zeitschrift für Religion, Gesellschaft und Politik, 2022)

Factors That Shape Mosque Archives A Multi-level Model - Müssig, Stephanie (Journal of Muslims in Europe, 2022)
In most mosque archives, the subject range seems to be limited to bureaucratic matters. In this article I discuss the factors that are responsible for this constraint. Using academic literature on (Christian) religious and (ethnic) community archives, as well as relying on the research presented in this special issue, I develop a hierarchical (or multi-level) model of subject ranges in mosque archives by considering factors at the individual, intermediate, and system level. I argue that the individual dispositions of mosque leaders regarding resources and attitudes, as well as funds at the intermediate level, are key to the maturing of the archiving culture in mosques.
Created from Fastlane, Scopus look-up
Keywords: archives; mosque; resources; subject range

Germany - Jaraba, Mahmoud; Nicolai, Katharina; Kühnel, Verena Margarete; Linke, Maximilian; Müssig, Stephanie; Nowar, Nina; Klingel, Julia (Yearbook of Muslims in Europe, 2019)

Germany - Nicolai, Katharina; Jaraba, Mahmoud; Klingel, Julia; Linke, Tibor; Müssig, Stephanie; Thielmann, Jörn; Weißert, Antonia (Yearbook of Muslims in Europe, 2021)

Introduction - Jonker, Gerdientje; Müssig, Stephanie (Journal of Muslims in Europe, 2022)

Muslime in Deutschland und die Rolle der Religion für die Arbeitsmarktintegration - Stichs, Anja; Müssig, Stephanie (Islam und die deutsche Gesellschaft, 2013)
Muslime bilden eine heterogene Gruppe, über die aus der amtlichen Statistik nur wenig bekannt ist. Gleichzeitig wird dem Merkmal der Religionszugehörigkeit in integrationspolitischen Debatten immer mehr Aufmerksamkeit geschenkt.<br

Muslimisches Leben in Deutschland - Haug, Sonja; Müssig, Stephanie; Stichs, Anja (2009)

Muslimisches Leben in Nordrhein-Westfalen - Haug, Sonja; Müssig, Stephanie; Stichs, Anja; Vardar, Nilden (2011)

Muslimische Verbände aus Sicht der muslimischen Bevölkerung - Stichs, Anja; Haug, Sonja; Müssig, Stephanie (Zeitschrift für Ausländerrecht und Ausländerpolitik, 2010)

Muslim Life in Germany - Haug, Sonja; Müssig, Stephanie; Stichs, Anja (Bundesamt für Migration und Flüchtlinge, 2009)

Muslims' Day-to-Day Handling of Property and the Adherence to Islamic Norms: A Systematic Review of Studies for Western Europe - Müssig, Stephanie (Journal of Muslims in Europe, 2015)
The aim of this work is to answer the question: "What role do Islamic norms play in property-related attitudes and behaviour of Muslims living in Western European societies?" To this end, a systematic review of electronic journal databases was undertaken to identify academic works published on the matter up to August 2013. Twenty relevant papers were identified, all of which contained original data. The empirical results of the studies show that Muslims in Western Europe incorporate Islamic norms in their decisions in everyday situations and secular life.
Created from Fastlane, Scopus look-up
Keywords: attitudes; behaviour; economy; Islam; Muslim; property; religion; religious norms

Normen - islamisch - Müssig, Stephanie (Lexikon für Kirchen- und Religionsrecht, 2020)

Politische Einstellungen und politische Partizipation von Migranten in Deutschland - Müssig, Stephanie; Worbs, Susanne (2012)

Politische Partizipation von Menschen mit Migrationshintergrund in Deutschland - Müssig, Stephanie (Springer VS Wiesbaden, 2020)
Eine politikwissenschaftliche Studie<br
Keywords: Politische Partizipation von Menschen; Migrationshintergrund; Deutschland; Quantitativ-empirische Analyse; Migranten; erste Generation; zweite Generation; Politische Integration; Wahlbeteiligung; Politische Ungleichheit; Nichtelektorale Partizipation; Politische Kultur; Civic Voluntarism Model; Protest; Parteinahe Aktivitäten; Ausländer; Politische Rechte

Recht und Moral - islamisch - Müssig, Stephanie (Lexikon für Kirchen- und Religionsrecht, 2020)

Researching Mahr in Germany: A Multidisciplinary Approach - Günther, Ursula; Herzog, Martin; Müssig, Stephanie (Review of Middle East Studies, 2015)
This article considers the legal institution of mahr in Islamic family law from three research perspectives in order to provide insights into the phenomenon's complexity, particularly with regard to current legal practices. In particular, emphasis is placed both on countries where family law is shaped by Islamic traditions (e.g., Morocco) and on countries whose legal traditions do not have a mahr counterpart (e.g., Germany). First, the social and economic function of dower will be described. As a special form of property transfer, mahr will be analyzed in its historical and present shape in theory and practice. Second, the legal conceptualization of mahr in the German legal context will be discussed. The example of Morocco serves to illustrate the changes with regard to mahr because of the process of incorporation of Islamic legal concepts into a national statutory law system. Given the Muslim diaspora, these insights are important contributions to the legal intepretation of mahr in a transnational context.<br
Keywords: mahr; family law; property transfer; marriage; Muslim diaspora; Islam in Germany; legal practices; transnational contexts of family law; mahr; family law; property transfer; marriage; Muslim diaspora; Islam in Germany; legal practices; transnational contexts of family law

Rezension zu Benn, Tansin; Pfister, Gertrud; Jawad, Haifa (eds.). 2011. Muslim Women and Sport. London: Routledge. - Müssig, Stephanie (2012)

Rezension zu Drieskens, Barbara; Mermier, Franck; Wimmen, Heiko (eds.). 2007. Cities of the South, Citizenship and Exclusion in the 21st Century. Beirut: SAQI - Müssig, Stephanie (2009)

Rezension zu Hermann, Katja. 2008. Selbstorganisation und politische Partizipation der palästinensischen Minderheit in Israel. Berlin: Schwarz Verlag. - Müssig, Stephanie (2008)

Rezension zu Hopkins, Peter; Gale, Richard (eds.). 2009. Muslims in Britain. Race, Place, Identities. Edinburgh: Edinburgh University Press. - Müssig, Stephanie (2010)

Turkish Mosque Archives in Industrial Towns in Southern Germany: An Ethnographic Survey - Jonker, Gerdientje; Elbel, Isabel; Klein, Arne; Klopke, Jule; Müssig, Stephanie; Schönstedt, Jens; Ulbricht, Victoria (Journal of Muslims in Europe, 2022)
Starting from the thesis that European mosque archives offer important sources for the history of Muslims and Islam in Europe, this contribution presents results of a pilot survey into the whereabouts of mosque archives in Germany. Focusing on five small towns in industrial zones where predominantly Turkish contract workers have settled, we asked Turkish mosque administrators, chairmen and imams how they had handled papers in the past, whether and where they had stored folders that were not in use anymore, and what kind of documents their collections contained. What we found were various archival records in a wide and unexpected range of places. We also learned that our questions prompted very different reactions. Umbrella organisations understood their archives as tools for preserving the written sources documenting their origins, whereas local administrators tended to see them as records of their personal memories. Our conclusion is that the time is ripe for the development of knowledge about mosque archives in Germany and, with regard to the founding generation, this is of crucial importance.
Created from Fastlane, Scopus look-up
Keywords: ethnographic survey; Germany; history of Muslims; mosque archives

Yearbook of Muslims in Europe - Akgönül, Samim; Alibasic, Ahmet; Müssig, Stephanie; Nielsen, Jørgen S.; Racius, Egdunas (Brill, 2022)

Yearbook of Muslims in Europe - Akgönül, Samim; Alibasic, Ahmet; Müssig, Stephanie; Nielsen, Jørgen S.; Racius, Egdunas (Brill, 2023)

Yearbook of Muslims in Europe - Müssig, Stephanie; Racius, Egdunas; Akgönül, Samim; Alibasic, Ahmet; Nielsen, Jørgen S.; Scharbrodt, Oliver (Brill, 2021)

Yearbook of Muslims in Europe - Racius, Egdunas; Müssig, Stephanie; Akgönül, Samim; Alibasic, Ahmet; Nielsen, Jørgen S.; Scharbrodt, Oliver (Brill, 2020)

Zur Rolle von muslimischen Konvertierten im Gemeindeleben - Vardar, Nilden; Müssig, Stephanie (2011)